Integration Model: Intellectual Capital and Financial Risk to Improve Financial Performance of Conventional Banks in Indonesia - Muuna, Adellya Nihayatul; Bawono, Andy Dwi Bayu; Witono, Banu (Universitas Muhammadiyah Surakarta, 2024)
Purpose: Conventional Banks are banks that have large credit growth in Indonesia. Conventional Bank credit grew by an average of 7.99% per year during 2015-2020. The continuous occurrence of non-performing loans is one of the main causes of the failure of the banking system. During the global Covid-19 pandemic crisis, banks had to face internal problems, namely the many cases of customer money loss and after the Covid-19 pandemic, banking risks were still not completely normal. This study develops previous research by adding the Risk Profile variable, using different indicators in measuring liquidity risk variables and focusing research on conventional banking to assess relevant financial performance. Methodology: This study uses a quantitative method. This study uses secondary data taken from the annual reports of each company in the financial ratio table. The sampling used by the researcher is Purposive Sampling. The population used is conventional banks listed on the IDX in 2020-2023. The total number of banking companies registered during the 2020-2023 period was 43 banks. The sample in this study was obtained as many as 88 consisting of 22 conventional banking companies. The data analysis technique in this study used multiple linear regression analysis with classical assumption tests in the form of normality tests, multicollinearity tests, heteroscedasticity tests, and autocorrelation tests with SPSS 25 analysis tools. As well as hypothesis testing with F tests and t tests. Results: Intellectual capital as measured by Human Capital Efficiency (HCE) has a significant negative effect on financial performance with a significance value of 0.000, the beta value shows a negative value, and with the HCE t-count value (-5.271) which is smaller than the t-table value (-1.98932). Capital Employee Efficiency (CEE) has a significant positive effect on financial performance with a significance level value of 0.013 and the CEE t-count value (2.539) is greater than the t-count (1.98932). Structural Capital Efficiency (SCE) and Loan to Deposit Ratio (LDR) do not affect financial performance because the t-count value of SCE (0.894) t-table value (-1.98932), the significance value of SCE and LDR is greater than 0.05, respectively, namely SCE (0.374) and LDR (0.345). Meanwhile, credit risk as measured by Non Performing Loan (NPL) has a significant positive effect on BOPO with the t-count value of NPL (3.465) which is greater than the t-table value (1.98932) and the significance value of 0.005 is less than 0.05. The independent variables simultaneously have a significant effect on BOPO because the F count value (28.924) exceeds the F table value (2.324) and the significance level (0.000) is lower than the alpha threshold set (0.05). Applications/Originality/Value This study recommends are used as input for companies in an effort to maximize the potential of intangible assets owned by the company and risk management in managing financial ratios and bank asset quality to improve the efficiency of banking financial performance to maintain banking sustainability. The difference between this research and previous research is the addition of the Credit Risk variable, using different indicators in measuring the financial performance variable, and placing financial technology as a moderating variable, as well as focusing the research on conventional banking for relevant financial performance assessments.